2020
DOI: 10.1002/jcp.30085
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelium tissue engineering: An evolution of signaling molecules, cells, and scaffolds toward 3D bioprinting and cell sheets

Abstract: Cornea is an avascular and transparent tissue that focuses light on retina. Cornea is supported by the corneal‐endothelial layer through regulation of hydration homeostasis. Restoring vision in patients afflicted with corneal endothelium dysfunction‐mediated blindness most often requires corneal transplantation (CT), which faces considerable constrictions due to donor limitations. An emerging alternative to CT is corneal endothelium tissue engineering (CETE), which involves utilizing scaffold‐based methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 268 publications
(587 reference statements)
0
22
0
Order By: Relevance
“…Typically, a 3D image of the cornea is created via ultrasound or optical coherence tomography (OCT), though a Scheimpflug camera can be used as well [ 12 , 17 ]. The ideal printing medium, referred to as “bioink,” must have the mechanical strength to withstand the shear stress of extrusion through the nozzle, retain adequate transparency, support cell viability, allow diffusion of nutrients and oxygen, be suturable, and be biodegradable [ 1 , 14 ]. They often must be cross-linked to maintain their structure [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, a 3D image of the cornea is created via ultrasound or optical coherence tomography (OCT), though a Scheimpflug camera can be used as well [ 12 , 17 ]. The ideal printing medium, referred to as “bioink,” must have the mechanical strength to withstand the shear stress of extrusion through the nozzle, retain adequate transparency, support cell viability, allow diffusion of nutrients and oxygen, be suturable, and be biodegradable [ 1 , 14 ]. They often must be cross-linked to maintain their structure [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…They often must be cross-linked to maintain their structure [ 18 ]. Optics is one of the biggest challenges, as the process requires sufficiently high resolution for a smooth surface and involves printing flat layers into a curved structure [ 1 ]. Multiple authors have described promising results in meeting the above parameters, but the ultimate challenge remains in building toward a multilayered and fully replicative structure [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one of the future challenges lies in designing tissue substitutes that provide the characteristics of the Descemet's membrane (DM), as studies have shown that the DM is crucial as a substrate in damaged corneal endothelium (CE) regeneration [127]. This has led to researchers bioengineering constructs that are able mimic the DM properties such as (i) physiochemical properties, (ii) 3D architecture and (iii) mechanical properties in order to facilitate the support of functional corneal endothelium as that in the in vivo cornea [78].…”
Section: Endotheliummentioning
confidence: 99%
“…Most of the current culture media formulations for CEC expansion contain xenogeneic components, such as animal serum, which makes such media incompatible with strict clinical requirements. This problem can be partially solved by the substitution of animal serum with human serum [ 75 ], modified platelet lysate [ 76 ], or other recombinant proteins and small-molecule compounds [ 77 ] that have recently been used for CE ex vivo expansion.…”
Section: In Vitro Expansion Of Cells From Donor Tissuementioning
confidence: 99%